Interprosthetic Femur Fractures: A Review Article. Issue 9 (22nd September 2022) - McMellen, Christopher J.; Romeo, Nicholas M.
Abstract : ➢ The prevalence of interprosthetic femur fractures (IFFs) is rising with the aging population and increased prevalence of total joint arthroplasty. ➢ IFFs have high rates of complications and high associated morbidity and mortality. ➢ The main treatment methods available for IFFs include plate fixation, intramedullary nailing, combined plate fixation and intramedullary nailing, and revision arthroplasty including partial and total femur replacement. ➢ There have been several proposed classification systems and at least 1 proposed treatment algorithm for IFFs; however, there is no consensus. ➢ Whichever treatment option is chosen, goals of surgery should include preservation of blood supply, restoration of length, alignment, rotation, and sufficient stabilization to allow for early mobilization.